AB0189 Interleukin-6/Stat Pathway is Responsible for the Induction of REG Iα, A New Auto-Antigen in SjÖGren's Syndrome Patients, in Salivary Duct Epithelial Cells. (10th June 2014) - Fujimura, T.; Fujimoto, T.; Itaya-Hironaka, A.; Miyaoka, T.; Kondo, S.; Yoshimoto, K.; Sakuramoto-Tsuchida, S.; Yamauchi, A.; Takeda, M.; Tsujinaka, H.; Tanaka, Y.; Takasawa, S.
Abstract : Background: The regenerating gene, Reg, was originally isolated from a rat regenerating islet cDNA library, and its human homologue was named REG Iα . Reg gene product acts as a growth factor and is important for various inflammatory diseases. Sjögren's syndrome (SS) is chronic autoimmune disease characterized by inflammation of salivary and lacrimal glands, and local or systemic overexpression of pro-inflammatory cytokines is involved with the pathogenesis. Recently, we reported that REG Iα mRNA as well as its product (REG Iα protein) were overexpressed in ductal epithelial cells in the minor salivary glands (MSG) of SS patients (1). Furthermore, auto-antibodies against REG Iα were found in SS patients and the anti-REG Iα auto-antibody positive group showed significant lower saliva secretion (1). Although some correlations between expressions of REG family genes and cytokines were reported (1), which cytokine is responsible for REG Iα expression in MSG has been elusive. Objectives: This study was undertaken to elucidate the role of cytokines for induction of REG Iα in salivary glands of Sjögren's syndrome patients. We examined which cytokines are responsible for REG Iα transcription in salivary ductal epithelial cells. Methods: REG Iα promoter (-1190/+26) was inserted upstream of a luciferase reporter gene in pGL3-Basic vector. The promoter plasmid was introduced by lipofection into human NS-SV-DC cells and A5 rat salivary ductal cells. After 6 hours, the cells were treated with interleukin (IL)-6 (20 ng/ml), IL-8 (100 nM), IL-22 (10 ng/ml), interferon (IFN)-β (1, 500 units/ml), and combination of them. After further 24 hour, the cells were harvested and transcriptional activity of REG Iα was measured by luciferase assay. Results: We found that IL-6 stimulation significantly enhanced the REG Iα promoter activity in human NS-SV-DC cells and A5 rat salivary ductal cells. Treatment with neither IL-8, IL-22, nor IFN-β changed the transcriptional activity of REG Iα . To identify the regions necessary for activation of REG Iα promoter by IL-6, progressive deletions of the REG Iα promoter were performed. Deletion analysis revealed that the region of -141 to -117 of the REG Iα gene was responsible for the promoter activation by IL-6. This region contains a consensus sequence for signal transduction and activation of transcription (STAT). Site-directed mutations of STAT-binding site in the region of REG Iα significantly attenuated promoter activation by IL-6. Conclusions: The present study showed that REG Iα transcription in salivary ductal cells was stimulated by IL-6. Our study also suggested STAT3 bound the consensus sequence of REG Iα promoter and regulated transcription in ductal epithelial cells in response to IL-6 stimulation. It was suggested that overexpression of REG Iα protein in salivary ductal cells is dependent on IL-6/STAT pathway and IL-6/STAT dependent REG Iα induction may play a role in the pathogenesis of SS. References: Yoshimoto K et al. Clin Exp Immunol 2013; 174: 1-9. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2813